Growth and Characterization of Radiation Sensors Based on Single Crystals of Hybrid Metal–Organic Methylammonium Lead Bromide and Iodide Perovskite. Issue 11 (31st August 2020) - Murgulov, Valeria; Daub, Michael; Hillebrecht, Harald; Fiederle, Michael; Franc, Jan; Dědič, Václav
Abstract: The inverse temperature (T)‐dependent methods yield single crystals of methylammonium lead halide perovskite with strained lattices. In contrast, the antisolvent diffusion method (antisolvent‐vapor crystallization (AVC)) produces unstrained MAPbBr3 crystals with more uniform growth features and lower density of defects. The powder X‐ray diffraction (XRD) measurements confirm the cubic and the tetragonal structure of the MAPbBr3 and the MAPbI3 samples, respectively. The XRD pole figure measurements (MAPbBr3 ) reveal a roughly parallel dominant (100) lattice plane to the sample surface. An optimal crystal growth combines growth of a seed on an oriented substrate by the AVC method followed by either the AVC or a T‐dependent method. The estimated resistivity ρ and the density of trap state n trap values for the MAPbI3 samples are 10 7 Ωcm and 10 10 cm −3, respectively. The X‐ray detection test reveals promising electrical properties of the MAPbI3 material. Results from the Hall measurements in van der Pauw geometry for the MAPbBr3 samples agree with those in the literature: the charge‐carrier concentration of 10 9 −10 10 cm −3 and the mobility of 7–289 cm 2 V −1 s −1, n trap of 10 9 −10 10 cm −3, and ρ of 10 7 –10 8 Ωcm. These electrical parameters indicate that the MAPbBr3 samples satisfy requirements for radiation sensors. Abstract : The inverse temperature (T)‐dependent and T‐independent solution methods yield single crystals of methylammonium lead halide perovskite (MAPbBr3 and MAPbI3 ) radiation sensors. The X‐ray radiation test confirms suitability of the MAPbI3 semiconductor material for X‐ray sensing. The higher resistivity and mobility values for the MAPbBr3 samples indicate that this perovskite material also satisfies the requirements for radiation sensors.